THE PROBLEMS OF POLICY IN MODERN WORLD AS THE SUBJECT OF PHILOSOPHY REFLECTION - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problems of contemporary world politics generated by the phenomena of globalization and informatization have been analized in this article.